Women resistance in han kang’s the vegetarian - Ivan Edgar; Y.B. Agung Prasaja (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2026)
This thesis analyzes women's resistance in Han Kang's The Vegetarian using a feminist literary approach. This study applies the concepts of Carol J. Adams and Judith Butler to examine the protagonist, Yeong-hye. This research aims to identify the forms of resistance she performs, the causes that trigger her resistance, and the effects of her resistance as responded to by her surrounding environment. The research employs a qualitative descriptive method, supported by textual analysis of narrative events, dialogue, and character dynamics. The findings reveal that women's resistance appears in two primary forms. The first is the restoration of the absent referent, manifested through Yeong-hye's refusal to eat meat, her rejection of domestic and sexual duties, her abandonment of the bra, and her aspiration to become a plant. The second is gender as phantasm, reflected in her family's perception of her as an existential threat that must be eliminated. Furthermore, the study concludes that the causes of her resistance include awareness of the absent referent, failed interpellation, and anti-gender ideology as an external trigger. Meanwhile, the effects of her resistance are shown through the disruption of patriarchal symbolism, punishment for gender deviance, and her position as the abject who ultimately finds freedom in her expulsion.